Integrated strategy to control wilt disease of cumin (Cuminum cyminum L.) caused by Fusarium oxysporum f. sp. cumini (Schlecht) Prasad & Patel - G Lal, Deepak bijarniya, (Journal of Spices and Aromatic Crops, 2009)
Various fungicides, oilcakes and fertilizers were evaluated at Jaipur (Rajasthan) for themanagement of cumin (Cuminum cyminum) wilt caused by Fusarium oxysporum f. sp. cumini.Trimethyl thiuram disulphide (0.1 g g-1 seeds) was the best fungicide which was on par withpropiconazole, carbendazim and copper oxychloride (0.1 g g-1 seeds) for the control of wilt.The disease incidence was minimum under the soil treatment with neem cake (30 q ha-1)which was on par with sesamum cake (25 q ha-1). Among the chemical and non-chemicalmanures, application of NPK @ 40 kg ha-1 was most suitable to control the disease whichwas on par with Azotobacter @ 40 kg ha-1. The disease incidence was also significantly lowerin plants grown in solarized soil. The yield was significantly higher in all treatments ascompared to control. The highest cost : benefit ratio was obtained (1:40) in thiophanatemethyl treatment followed by carbendazim. Among the combined treatments, minimumdisease incidence was recorded with solarized soil + sesamum cake @ 25 q ha-1 + seed treatmentwith carbendazim @ 0.1 g g-1 seeds followed by solarized soil + sesamum cake @ 25 q ha-1 +Azotobacter @ 40 q ha-1. However, the highest cost : benefit ratio (1:10.6) was obtained withsolarized soil + sesamum cake @ 25 q ha-1 + Azotobacter (biofertilizer) @ 40 kg ha-1. Theintegrated treatments recorded the highest grain yield and low disease incidence over controlas compared to individual application.